IMPLEMENTATION OF HALO CAPIL SERVICES IN POPULATION ADMINISTRATION SERVICES IN PADANG LAWAS REGENCY - Yulia Rahmadani Hrp; Ti Aisyah; Risna Dewi; Muhammad Hasyem (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Population services are crucial public services because they directly relate to the provision of citizens' civil rights. In an effort to improve the quality and effectiveness of services, the Population and Civil Registration Office of Padang Lawas Regency has launched the Halo Capil Service as a technology-based service innovation through the WhatsApp application. This service provides easy access to information and facilitates the submission of population documents such as Family Cards and birth certificates. However, its implementation has not been optimal, mainly due to a lack of clear information and minimal socialization, resulting in rural communities lacking understanding of the service's purpose and benefits. This study aims to describe the implementation of the Halo Capil Service in population services in Padang Lawas Regency. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The research analysis refers to the Edward III policy implementation model, which includes aspects of communication, resources, disposition, and bureaucratic structure. The results show that service implementation has not been optimal due to limited human resources, network constraints, and a lack of socialization and infrastructure support.